Racemoramus panicula Calder 2012, comb. nov. - Calder, Dale R. (Zenodo, 2012)
Racemoramus panicula (G.O. Sars, 1874), comb. nov. Fig. 24 Campanulina panicula G.O. Sars, 1874: 121, pl. 5, figs. 9–13.— Kramp, 1941: 4, fig. 5.— Rees & Rowe 1969: 17.— Jägerskiöld, 1971: 61.— Cornelius, 1995a: 192, fig. 43D. Type locality. Norway: Oslofjord, 50–60 fm (91–110 m) (G.O. Sars 1874: 121). Museum material. Kosterhavet, 58°53.093’N, 11°05.668’E, 20–30 m, 09.ix.2010, biological dredge, R / V Nereus , two colonies or colony fragments, each with many hydrocauli, up to 3.8 cm high, on polychaete tubes and ascidians, without gonophores, ROMIZ B3916. Remarks. Kramp (1941) provided a thorough description of Opercularella panicula (G.O. Sars, 1874) based on specimens from Norway and Sweden, and remarked on its similarity to Campanulina denticulata Clarke, 1907 from deep waters of the eastern tropical Pacific (Clarke 1907) and Sagami Bay, Japan (Stechow 1913). Leloup (1974) discounted seeming differences between the two as ecologically induced and regarded them as conspecific. Vervoort (1966) referred Campanulina indivisa Fraser, 1948, from bathyal depths off California, to the synonymy of O. denticulata . Subsequent authors have mostly agreed that these are all synonyms. Nevertheless, their combined range is so extensive that it raises doubts whether a single species is represented. In addition to records in the eastern Atlantic (e.g., Cornelius 1995a, as Campanulina panicula ), similar hydroids have been reported from deep waters in the western Pacific (Stechow 1913: as Campanulina denticulata Hirohito 1995: as Opercularella panicula Schuchert 2003: as Campanulina panicula ), the eastern Pacific (Clarke 1907: as Campanulina denticulata Fraser 1948: as Campanulina (?) indivisa Leloup 1974: as Opercularella panicula ), and the Indian Ocean (Vervoort 1966: as? Opercularella denticulata ). Schuchert (2003) reported that materials from Indonesia were indistinguishable from those examined earlier from Iceland (Schuchert 2001a), supporting the hypothesis that a single species is represented. Its ...